A SEMANTIC ANALYSIS ON ONOMATOPOEIA IN “JOKER” MOVIE SCRIPT - Sujatna, Meita L.; Valeria, Tasya; Fazri, Muhamad Alfi; Nurzaman, Muhamad N. Jihad; Fauzi, Farhan; Febristy, Della Shafira (CENTRAL ASIA AND THE CAUCASUS, 2022)
As one of the types of figurative language, onomatopoeia is commonly used in every context, even in entertainment products such as films. "Joker", a movie released in 2019, is no exception. It relies on the different sub-types of onomatopoeia to describe actions or to be part of the dialogues as the transcript demonstrates. This study focuses on the use of onomatopoeia in the movie, especially 1) the frequency of various subtypes of onomatopoeia that appear in Joker’s movie script, 2) whether they appear in the dialogues or the description, and 3) how their usage helps to build the messages conveyed in the movie. It employed the qualitative descriptive approach to provide a description of how onomatopoeia is used in various scenes and circumstances found in the movie. From the 47 data found, 17 (68%) were considered unique, while the remaining 8 (32%) are variants of the unique words. There was more onomatopoeia found in the description (38 data or 81%) than in the dialogues (9 data or 19%); the most frequent sub-type was that of mechanical sound. Even though almost all the data were lexically well-established, the contribution to meaning was highly dependent on context. It may be concluded that the dominant sub-type replicates the paralinguistic communication by human and non-human characters, while the least frequent was due to no animal or its resemblance appearing in the movie. The research suggests that more investigation may be needed into similar film genres to justify or refute the findings of the study.